2011
DOI: 10.1007/s00228-011-1028-1
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of laboratory measurement and hyperkalaemia in hospitalised patients using serum potassium concentration increasing drugs

Abstract: PurposeAlthough, drug–drug interactions (DDIs) between potassium-increasing drugs (PIDs) are known risk factors for developing hyperkalaemia, not much is known about their risk and management strategies during hospitalisation. This study examines the frequency of serum potassium measurements and hyperkalaemia in hospitalised patients, based on the use of one or more PIDs, and the determinants thereof.MethodsAdult patients hospitalised in the University Medical Centre Utrecht between 2006 and 2008 were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
2
11
1
Order By: Relevance
“…A cross‐sectional study from 1995 of diabetes outpatients in the UK, found that 15% of the individuals had a serum potassium level >5.0 mmol/l over a 12‐month period, and that hyperkalaemia was also common among people with normal kidney function and in those not receiving drugs known to have an effect on potassium levels . In line with our findings, studies have documented an increasing risk of hyperkalaemia in patients with progressively worsening kidney function and in patients with heart failure , as well as among those receiving renin angiotensin aldosterone system inhibitors and in those with advanced age . Although it is well‐known that hyperkalaemia is associated with increased ventricular arrhythmias and may be associated with other adverse outcomes , to the best of our knowledge, there have been no previous studies of these associations specifically in people with diabetes.…”
Section: Discussionsupporting
confidence: 88%
“…A cross‐sectional study from 1995 of diabetes outpatients in the UK, found that 15% of the individuals had a serum potassium level >5.0 mmol/l over a 12‐month period, and that hyperkalaemia was also common among people with normal kidney function and in those not receiving drugs known to have an effect on potassium levels . In line with our findings, studies have documented an increasing risk of hyperkalaemia in patients with progressively worsening kidney function and in patients with heart failure , as well as among those receiving renin angiotensin aldosterone system inhibitors and in those with advanced age . Although it is well‐known that hyperkalaemia is associated with increased ventricular arrhythmias and may be associated with other adverse outcomes , to the best of our knowledge, there have been no previous studies of these associations specifically in people with diabetes.…”
Section: Discussionsupporting
confidence: 88%
“…2); (ii) diabetes mellitus [6,31]; (iii) the highest risk concerned pulmonary allograft, mainly due to PID combinations of immunosuppressive agents, trimethoprim, and ACE inhibitor [32,33]; (iv) female gender, confirming another analysis of gender as a predictor in drug-induced hyperkalaemia [34]; (v) elevated serum potassium (> 4.5 mEq/l) at onset of the DDI. 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 In contrast to other studies, we couldn't establish an association between hyperkalaemia during potassium-increasing DDIs and age or hospitalisation in surgical versus non-surgical specialties [12].…”
Section: Hyperkalaemiacontrasting
confidence: 91%
“…However, unspecific alerts will lead to alert fatigue [7][8][9]. The present study improves the understanding of factors associated with hyperkalaemia [12] and adds physician-related factors, which may help to design more specific alerts.…”
Section: Hyperkalaemiamentioning
confidence: 90%
See 2 more Smart Citations